Evaluation of Conceptual Group Therapy Model Based on Acceptance and Commitment on Procrastination of Iranian Adolescents - Nesa Javid Jahromi; Nadereh Sohrabi Shegefti; Hossin Baghuly; Hojatollah Javidi (مطالعات روانشناختی, 2025)
Procrastination is a significant challenge in the daily and academic lives of adolescents, leading to psychological concerns and decreased performance. This study aimed to evaluate a conceptual model of group therapy based on Acceptance and Commitment Therapy to reduce procrastination among Iranian adolescents. The research employed a developmental approach utilizing a sequential exploratory mixed-methods design. In the qualitative phase, semi-structured interviews were conducted with 17 university professors and counselors. For the quantitative phase, a researcher-developed questionnaire consisting of 35 items was distributed to 40 experts. Data were analyzed using thematic analysis and confirmatory factor analysis in PLS software. The resulting conceptual model comprised five dimensions: self-help skills, operational framework of group therapy, mindfulness, commitment and values clarification, and group support, with a total of 35 foundational themes. The convergent validity values for all dimensions were satisfactory, and only two items needed to be removed. The findings indicate that group therapy based on Acceptance and Commitment Therapy can serve as an effective approach for reducing procrastination among adolescents. Furthermore, it is recommended that this approach be implemented in schools and counseling centers to enhance adolescents’ responsibility and self-regulation.